Worries a lift-the-flap book about friendship - Archer, Mandy; Forshaw, Louise (London Pat-a-Cake, 2021)
This fun lift-the-flap book helps reassure common preschool worries and encourages children to talk about their feelings. Find Out About: Worries helps curious preschoolers through common anxieties - like separation anxiety and fear of the dark - an encourages mindful thinking and empathetic behaviour. Featuring friendly child characters and familiar situations, they will find answers and reassurance when they are feeling worried. With fun flaps to lift and a memory game at the end, this is an excellent book for children and parents to share together
Education
Keywords: Emotions in children; Worry in children Juvenile literature; Worry in children